The Migration of the Japanese from the Center of Turan to the East - Lafasov, Urak (The journal of contemporary issues in business and government, 2021)
This article discusses the following issues, such as the fact that Japan is the easternmost border in the Great Turan region, the map of Turan drawn by the famous scholar Maḥmūd al-Kāšġarī, the ancient original name of Japan Jabarqa and its meaning “land”, the current name of Japan Jiben (Neppon) about the creation of Europeans. It is also known that the ancient inhabitants of Japan migrated from Central Asia and Southeast Asia to the present islands, the commonality of the remains of a Buddhist temple found in the ruins of the ancient city of Ayritom on the banks of the Amu Darya with temples in Japan, that the Japanese people were ethnically descended from the Ayns (Aynli, Aynli) who are still preserved in the Turkic peoples, and that the Ayns who remained in Central Asia were assimilated into the Kutchi and Kangrat tribes, the fact that the Uzbek kutchi tribes logo is circular in shape and is associated with the circular symbolism of the sun on the Japanese flag, the division of the Aynli into October and Karaton, the places where the Aynli now live in Uzbekistan, the regions associated with the name chiya (sakura) are reported to have preserved some lexical units peculiar to the Turkic languages in Japanese. In turn, the history of Uzbek-Japanese relations dates back to ancient times, the spread of Buddhism in Japan, Nisi Tokudziro, a Japanese traveler, wrote a book called “Turkestan Travelogue”; Japanese researchers Yasumashi Fukushima, Kazuo Otani, Masaji Inoue and Zuicho Toshibana visited our country; In the field of education, the teacher Itaro Kumatsu wrote textbooks for the Japanese “Uzbek language” (1978), “Uzbek conversation” (1983), “Uzbek-Japanese dictionary” (1980, 1985), it commented that the funds allocated by the Japanese government for Uzbekistan and soft loans are spent on the development of our country. The necessary scientific conclusions were drawn from the above data.